Microwave absorption and anti-aging properties of modified bitumen contained SiC attached layered double hydroxides. (10th December 2019) - Li, Chao; Wu, Shaopeng; Shu, Benan; Li, Yuanyuan; Chen, Zongwu
Highlights: SiC particles can adhere to LDHs and form stable synthetic products. Increasing complex permittivity of SiC attached LDHs results in the enhancement of microwave absorption. SiC attached LDHs enhance the high temperature rheological properties of the pure bitumen. SiC attached LDHs can effectively improve the anti-aging properties of bitumen. Abstract: Layered double hydroxides (LDHs) is typical anti-aging modifier used in bitumen. But LDHs meets obstacle that it cannot improve the self-healing ability of bitumen, which is associated with the healing efficiency of cracks caused by aging and high-temperature rutting. SiC is well microwave absorber that can release heat and accelerate the self-healing process of bitumen under microwave radiation. Thus, this paper envisaged the feasibility of SiC attached LDHs to enhance the microwave absorption and anti-aging performance of modified bitumen simultaneously. The surface morphology, phase composition and microwave absorption properties of the SiC attached LDHs were measured. Subsequently, three types of modified bitumen were prepared by mixing pure bitumen and the SiC attached LDHs according to the three amounts of 0%, 2% and 4% (by mass of pure bitumen). The effects of the SiC attached LDHs on the high temperature rheological properties and anti-aging properties of modified bitumen were also evaluated. Results show that the attached SiC and LDHs are fully fused together and form a stable product. The SiC attached LDHs improves the microwave absorption of modified bitumen significantly. Additionally, the SiC attached LDHs can slow down the viscous degradation of modified bitumen, and effectively improves the anti-aging performance.